Assessment of Condition and Medication Knowledge Gaps Among Atrial Fibrillation Patients: A Systematic Review and Meta-analysis. Issue 8 (August 2019) - Salmasi, Shahrzad; De Vera, Mary A.; Barry, Arden; Bansback, Nick; Harrison, Mark; Lynd, Larry D.; Loewen, Peter S.
Background: Patient education facilitates construction of a correct illness representation, improves beliefs about medications, and improves knowledge, factors that have been associated with better adherence.Objective: Our objective was to characterize the published literature about atrial fibrillation (AF) patients' disease and medication knowledge to identify knowledge gaps and misconceptions to inform AF patient education strategies.Methods: Following PRISMA guidelines, we searched PubMed, EMBASE, CINAHL, and PsychINFO from inception to May 2018 for studies that assessed AF patients' knowledge about their condition and medications. For quantitative studies, we extracted the proportion of participants who provided correct answers to the questions asked about their condition, medications, or risk of stroke. We classified data for related questions into knowledge domains. A random-effects meta-analysis was conducted for each knowledge domain. A domain was considered a knowledge gap if the pooled mean proportion of participants who demonstrated knowledge of it was ≤50%, regardless of CI. Qualitative data were summarized narratively.Results: A total of 21 studies were included. AF- and stroke-related knowledge gaps and misconceptions included the following: AF can be asymptomatic, AF can predispose to heart failure, women are at a higher risk of stroke, the definition of ischemic stroke, and patients' awareness of their diagnosis. Medication-related knowledge gaps were antithrombotic-drug interactions, antithrombotic-food interactions, vitamin K content of foods, the term INR (international normalized ratio) and its interpretation, and the required actions in case of a missed dose.Conclusion and Relevance: This systematic review identified several AF patient knowledge gaps about their condition and its treatment that can inform the development of AF patient education programs.